ANALISIS KETERAMPILAN BELAJAR (LEARNING SKILLS) DAN HASIL BELAJAR SISWA MELALUI PEMBELAJARAN DARING BERBASIS PADLET PADA MATA PELAJARAN GEOGRAFI - Erwin Pri Utomo; Nofrion Nofrion (Jurnal PIPSI (Jurnal Pendidikan IPS Indonesia), 2022)
Abstract.This research aims to analyze students’ learning skills and learning outcomes through Padlet-based online learning in Geography subject. This research is motivated by the low learning skills of students in Geography during online learning. One of the efforts that can be made to improve the learning process is to carry it out using the Padlet application. The type of research used is experimental research. The research subjects were students of class XI IIS 3 of SMA Pembangunan Laboratorium Universitas Negeri Padang as the experimental class and class XI IIS 4 as the control class. The data collection instruments used are students’ learning skill observation sheets and learning outcomes tests. The results of this research indicate that: (1) This research proves that students' learning skills are higher when learning with Padlet compared to other learning media in terms of critical thinking skills, communication skills, collaborative skills and creativity skills. (2) The research proves that there are differences in learning outcomes between the experimental class using the Padlet application and the control class without using the application. This is indicated by the obtained significance value (2-tailed) of 0.036 < 0.05 significance value. It means that there is a difference between the experimental class that was given special treatment by using the Padlet, which get a higher score than the control class that did not use the Padlet. So it can be concluded that the application of Padlet in learning is proven to be better in terms of students’ learning skills and learning outcomes in Geography subject.This research aims to analyze students’ learning skills and learning outcomes through Padlet-based online learning in Geography subject. This research is motivated by the low learning skills of students in Geography during online learning. One of the efforts that can be made to improve the learning process is to carry it out using the Padlet application. The type of research used is experimental research. The research subjects were students of class XI IIS 3 of SMA Pembangunan Laboratorium Universitas Negeri Padang as the experimental class and class XI IIS 4 as the control class. The data collection instruments used are students’ learning skill observation sheets and learning outcomes tests. The results of this research indicate that: (1) This research proves that students' learning skills are higher when learning with Padlet compared to other learning media in terms of critical thinking skills, communication skills, collaborative skills and creativity skills. (2) The research proves that there are differences in learning outcomes between the experimental class using the Padlet application and the control class without using the application. This is indicated by the obtained significance value (2-tailed) of 0.036 < 0.05 significance value. It means that there is a difference between the experimental class that was given special treatment by using the Padlet, which get a higher score than the control class that did not use the Padlet. So it can be concluded that the application of Padlet in learning is proven to be better in terms of students’ learning skills and learning outcomes in Geography subject.Abstrak. Penelitian ini bertujuan untuk menganalisis   keterampilan belajar (learning skills) dan hasilbelajar siswa melalui pembelajaran daring berbasis padlet pada mata pelajaran geografi. Penelitian inidilatar belakangi oleh  rendahnya keterampilan belajar (learning skills) siswa dalam pembelajarangeografi selama pembelajaran daring. Salah satu upaya yang dapat dilakukan untuk memperbaikiproses pembelajaran adalah dengan melaksanakan pembelajaran menggunakan aplikasi Padlet. Jenispenelitian yang digunakan adalah penelitian eksperimen. Subjek penelitian adalah peserta didik kelasXI IIS 3 SMA Pembangunan Laboratorium Universitas Negeri Padang sebagai kelas kelas eksperimendan kelas XI IIS 4 sebagai kelas kontrol. Alat pengumpulan data yang digunakan adalah lembarobservasi keterampilan belajar siswa dan tes hasil belajar. Hasil penelitian ini menunjukkan bahwa: (1)Penelitian ini membuktikan bahwa keterampilan belajar siswa lebih tinggi saat belajar dengan Padletdibanding dengan media pemelajaran lain yang dilihat dari aspek keterampilan berpikir kritis,keterampilan komunikasi, keterampilan kolaborasi dan keterampilan kreativitas. (2) Penelianmembuktikan bahwa terdapat perbedaan hasil belajar antara kelas eksperimen menggunakan aplikasiPadlet dengan kelas kontrol tanpa menggunakan aplikasi Padlet. Hal ini ditunjukan dengan diperolehnilai signifikansi (2-tailed) 0,036 < nilai signifikansi 0,05. Artinya terdapat perbedaan antara kelaseksperimen yang diberi perilaku khusus dengan menggunakan padlet mendapatkan nilai lebih tinggidibanding kelas kontrol yang tidak menggunakan Padlet. Sehingga dapat disimpulkan bahwapenerapan aplikasi Padlet dalam pembelajaran terbukti lebih baik dilihat dari keterampilan belajar(learning skills) dan hasil belajar siswa pada mata pembelajaran geografi. Keywords: Geography Learning, Study Skills, Padlet, Online learning